EXACT SOLUTIONS FOR A REACTION DIFFUSION EQUATION BY USING THE GENERALIZED TANH METHOD - GÓMEZ SIERRA, CESAR AUGUSTO; SALAS SALAS, ÁLVARO HUMBERTO (Scientia et Technica, 2007)
In this paper we present the generalized tanh method to obtain exact solutions of nonlinear partial differential equations. As a particular case, we obtain exact solutions for a reaction diffusion equation.